2016
DOI: 10.1098/rspb.2016.1329
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization as a facilitator of species range expansion

Abstract: Explaining the evolution of species geographical ranges is fundamental to understanding how biodiversity is distributed and maintained. The solution to this classic problem in ecology and evolution remains elusive: we still do not fully know how species geographical ranges evolve and what factors fuel range expansions. Resolving this problem is now more crucial than ever with increasing biodiversity loss, global change and movement of species by humans. Here, we describe and evaluate the hypothesis that hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
152
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 128 publications
0
152
1
Order By: Relevance
“…Pfennig et al. () demonstrated that hybridization could play a key role in the persistence of some populations at the edge of their range. Although hybridization among species of snook has not been observed in the wild (Tringali et al.…”
Section: Mean (Sd In Parentheses) Of Annual Water Temperature Wintermentioning
confidence: 99%
“…Pfennig et al. () demonstrated that hybridization could play a key role in the persistence of some populations at the edge of their range. Although hybridization among species of snook has not been observed in the wild (Tringali et al.…”
Section: Mean (Sd In Parentheses) Of Annual Water Temperature Wintermentioning
confidence: 99%
“…genetic rescue) or for new mutations to arise (Pfennig et al ., ). Such scenarios support the idea that IH may be correlated with the successful establishment and spread of alien invasive species (Lowe et al ., ; Pfennig et al ., ).…”
Section: Micropterus Dolomieu (Smb) and Micropterus Salmoides (Lmb) Imentioning
confidence: 98%
“…Freshwater fishes in particular have received considerable attention, as closely related species often display similar behavioural, biological and ecological characteristics, in addition to exhibiting external fertilization and high genomic compatibility (Hubbs, ; Kovach et al ., ; Mallet, ; Smith, ), thereby potentially increasing the likelihood of IH in these taxa. Such interspecific admixture may provide sufficient genetic variation, either through increased genetic diversity or via the transfer of adaptive alleles, to facilitate the establishment and spread of novel populations (Wilson & Bernatchez, ), while counteracting extinction by maintaining and increasing the size of hybrid populations (Drake, ), ultimately permitting population persistence (Pfenning et al ., ). This is of particular concern in an invasion context, as hybrids between native and invasive species may outcompete and displace native taxa (Mallet, ).…”
Section: Micropterus Dolomieu (Smb) and Micropterus Salmoides (Lmb) Imentioning
confidence: 99%
“…It is generally accepted that species' survival depends directly on their ability for adaptive evolution that is also a key component of range expansion (Pfennig et al, 2016). In each species, populations survive environmental change due to the production of alleles and epialleles for traits that are adaptive to the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, local adaptation is theoretically expected and has indeed been found to result mostly from admixture, more particularly from the hybridization of congeneric species (Abbott et al, 2013;Stelkens et al, 2014). In recent years, interspecific admixture involving repeated introgression in contact areas has been shown to be a facilitator of species range expansion by creating genetic variation that allows populations to adapt to selective pressures, either through the transfer of specific adaptive alleles, the selection of novel gene-combinations facilitating evolutionary innovation, or through the local increase of genetic and epigenetic diversity that allows the persistence of threatened populations (or species) and/or the creation of the conditions for further adaptation ( Bräutigam et al, 2013;Pfennig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%